Influence of microwave emanation on terms of fructification and productivity of tomatos - Z. U. Nasurlaewa; N. T. Gadjimusiewa; T. A. Аswarowa (Юг России: экология, развитие)
Low-intensive UHF radiation from the technical generator with the microwaves range of 18 cm and 21 cm on frequencies 1665 MHz and 1667 MHz renders stimulating influence on growth and development of plants of a tomato. It promotes earlier flowering and fructification and also raises productivity of plants of a tomato.